1995
DOI: 10.1029/94ja03145
|View full text |Cite
|
Sign up to set email alerts
|

The middle ultraviolet dayglow spectrum

Abstract: Spectroscopic measurements of the thermospheric dayglow in the wavelength range 1900 to 3400 Å are presented. These measurements were made during two rocket experiments conducted on March 30, 1990, and March 19, 1992, from White Sands Missile Range, New Mexico. The data are presented to provide reference spectra in the lower, middle, and upper thermosphere. The 1990 observations, which were made during high geomagnetic activity, showed considerably enhanced nitric oxide (NO) intensities. Self‐absorption theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Also, the complexity and weight of ground-based instrumentation may preclude missions to space. Nevertheless, the impact of airglow studies in space has been enormous, and there is a long list of successful flight programs in which airglow has been studied (Meier 1991;Broadfoot and Bellaire 1999;Budzien et al 1994;Eastes et al 1992;Cleary et al 1995;Hecht et al 2000;Minschwaner et al 2004;Stephan et al 2004), including Atmospheric Explorer (AE), the Upper Atmospheric Research Satellite (UARS), MSX, ARGOS, and the TIMED satellite. A prime example of long-term satellite monitoring of the atmosphere is the WINDII experiment on UARS, in which a Michelson interferometer has been used to look at a variety of dayglow and nightglow emissions and to study winds and temperatures over the 80-300 km range.…”
Section: Space-based Measurementsmentioning
confidence: 99%
“…Also, the complexity and weight of ground-based instrumentation may preclude missions to space. Nevertheless, the impact of airglow studies in space has been enormous, and there is a long list of successful flight programs in which airglow has been studied (Meier 1991;Broadfoot and Bellaire 1999;Budzien et al 1994;Eastes et al 1992;Cleary et al 1995;Hecht et al 2000;Minschwaner et al 2004;Stephan et al 2004), including Atmospheric Explorer (AE), the Upper Atmospheric Research Satellite (UARS), MSX, ARGOS, and the TIMED satellite. A prime example of long-term satellite monitoring of the atmosphere is the WINDII experiment on UARS, in which a Michelson interferometer has been used to look at a variety of dayglow and nightglow emissions and to study winds and temperatures over the 80-300 km range.…”
Section: Space-based Measurementsmentioning
confidence: 99%
“…It consists mainly of the Mg + 280 nm doublet, several NO bands and the 297 nm OI atomic line, see, for example, ref. 17. This 100 km spectrum serves as a reference spectrum for removing these thermospheric emission features from the mesospheric limb spectra.…”
Section: Isolating the Oh Signature In The Osiris Limb Spectramentioning
confidence: 99%
“…The O + ( 2 P‐ 4 S) doublet at 247.10 nm and 247.11 nm is the brightest feature of the middle ultraviolet (MUV) airglow above 200 km [ Cleary et al , 1995]. Only a handful of measurements have been made of this emission [ Feldman and Takacs , 1976; Cebula and Feldman , 1984; Cleary et al , 1995; Bucsela et al , 1998], but many experiments have observed the associated emission doublet at 732 nm and 733 nm from the O + ( 2 P‐ 2 D) transition [e.g., Walker et al , 1975; Rees et al , 1982; Torr et al , 1990; Fennelly et al , 1993; Broadfoot et al , 1997; Semeter , 2003] that shares the same excited state and thus derives from the same excitation processes. In the sunlight, photoionization and excitation of atomic oxygen is the primary source, while electron impact predominates in auroral regions [ Rees et al , 1982].…”
Section: Observationsmentioning
confidence: 99%